Nation‐dyadic history and cross‐border corporate deals: Role of conflict, trade, generational distance, and professional education - Arikan, Ilgaz; Arikan, Asli M.; Shenkar, Oded (Strategic Management Journal, 2020)
Abstract Research Summary This paper explores why and how nation‐dyadic history impacts aggregated firm decisions involving cross‐border activities (acquisitions, joint ventures, and alliances). We contextualize history and illustrate the negative effect of historical conflict on cross‐border deals. Nation‐dyads with historical conflict incorporate negative sentiments into their social and collective memories and national identities. Members of society assume the socially constructed national identity via primary and secondary socialization. National identities incorporate sentiments towards other nations and condition individuals' preferences, culminating in a preference‐biased search for or preference‐supporting evaluation of information concerning cross‐border deals. An increased generational distance from prior conflict and a higher percentage of graduates with common professional identities constructed by higher education in the social sciences, law, and business dampen the negative influence of historical conflict. Managerial Summary There is a reciprocal relationship between international trade and conflict across two nations: as the potential for conflict increases, trade levels fall, and as trade levels increase, the potential for conflict rises. We disentangle this relationship and determine the implications of historical conflict between two nations for cross‐border corporate deals (i.e., acquisitions/joint ventures/alliances). We show that, controlling for other factors, more frequent historical conflict discourages cross‐border corporate deals. We see this finding as a result of biased decision making based on preferences which reflect sentiments formed by national identities. Two mechanisms dampen the negative relationship between binational conflict and cross‐border deals: a higher percentage of business/law/social sciences graduates and a higher number of generations passed since the last conflict.